Towards a social psychology of precarity. (13th January 2023) - Coultas, Clare; Reddy, Geetha; Lukate, Johanna
Abstract: This article introduces the special issue 'Towards a Social Psychology of Precarity' that develops an orienting lens for social psychologists' engagement with the concept. As guest editors of the special issue, we provide a thematic overview of how 'precarity' is being conceptualized throughout the social sciences, before distilling the nine contributions to the special issue. In so doing, we trace the ways in which social psychologists are (dis)engaging with the concept of precarity, yet too, explore how precarity constitutes, and is embedded within, the discipline itself. Resisting disciplinary decadence, we collectively explore what a social psychology of precarity could be, and view working with/in precarity as fundamental to addressing broader calls for the social responsiveness of the discipline. The contributing papers, which are methodologically pluralistic and provide rich conceptualisations of precarity, challenge reductionist individualist understandings of suffering and coping and extend social science theorizations on precarity. They also highlight the ways in which social psychology remains complicit in perpetuating different forms of precarity, for both communities and academics. We propose future directions for the social psychological study of precarity through four reflexive questions that we encourage scholars to engage with so that we may both work with/in, and intervene against, 'the precarious'.